The use of supplementary materials in EFL classes: A comparative analysis of public and private high schools - Pinza Vizuete, Margarita Maricela (2012)
The present study explores the use of supplementary materials in EFL classes in public and private high schools. The main purpose of this research is to determine and analyze supporting materials used in EFL public and private high schools and compare the supporting materials used in both high schools in Quito. Qualitative and quantitative approaches were used for this research. Data collection formats like observation formats, questionnaires and charts were applied to gather information about the appropriateness, pertinence, and quality of the supplementary materials that were used in the two high schools. The sample included 120 adolescents ranging between 15 to 17 years of age that belonged to the 1st, 2nd, and 3rd senior private and public high schools, four English teachers, three female and one male; three from the public and one from the private high school. The findings of the study reveal that the frequency of use of supplementary materials was higher in the private high school than in the public one and in the last one the supporting materials used depended on the financial resources of the institution.